La valutazione della ricerca e suoi effetti sul lavoro scientifico - Emanuela Reale; Emanuela Varinetti (Quaderni di Sociologia)
The article discusses how external evaluation influences academic scientific work and modifies individual strategies for disseminating scientific results. Using a mixed-methods approach that integrates surveys, interviews, and the life histories of academics from Italian universities, the findings reveal a complex picture, such as a generalized increase in productivity across all disciplinary sectors and changes in publication practices, particularly in the social sciences and humanities. External evaluation, that is massive evaluation driven by the government, can have perverse effects, steering researchers towards topics and approaches more aligned with evaluative criteria, sometimes at the expense of innovation and exploratory research. The importance of structuring an evaluation system responsive to changes in scientific production across all disciplinary sectors is emphasized, recognizing the diversity of research practices while promoting quality, integrity, and creativity.